The Correlation between Students' Preferences and English Achievement in Hybrid Learning during Covid-19 Pandemic - Liya Astarilla Dede Warman (J-SHMIC : Journal of English for Academic, 2022)
The objective of this study was to investigate the correlation between university students’ preferences and their English achievement in hybrid learning. Correlational research design was utilized in this research. The participants of this study were 77 students from three universities in Pekanbaru, Riau. Random sampling technique was applied in choosing the participants in this study. The researcher collected the data of this study through questionnaire and achievement test. Descriptive statistical analysis namely correlation and regression analysis were applying to analyze the quantitative data. The findings revealed that there was a significant correlation between students’ preferences on their English achievement in hybrid learning with p-value 0.000<0.05 and correlation coefficient was 0.723. This result was categorized as a high or strong correlation. In addition, regarding to the results of regression analysis, R square was 0.522 which mean the influence percentage of university students’ preferences to students’ English achievement was 52.2%. The conclusion of this study that there was a strong correlation between students’ preferences in hybrid learning and their English achievement during COVID-19 pandemic.